Avaliação das causas e consequências da paralisação de obras públicas no âmbito do Tribunal de Justiça de Minas Gerais - Tiago Randazzo Rabelo (2023)
This research points out the main causes and consequences of the stoppage of works contracted by the Court of Justice of Minas Gerais (TJMG), from the study of the administrative processes that culminated in the termination of contracts with contractors, and identification of the costs involved in the process of resuming stalled works. The study identified and classified the causes of suspensions in the period prior to the effects of the Covid-19 pandemic, verified the technical, administrative and economic reasons that led to the suspensions and justified their recurrence. The studies were carried out on thirteen buildings of different sizes and regions in the State of Minas Gerais, built to house new forums of the Court of Justice. The main and secondary causes of stoppages were identified and grouped, and their consequences were assessed, taking into account in particular the financial risks associated with the time taken to restart work that had stopped. Finally, the main causes identified were compared with those found in the literature, analyzing the differences found for each situation. From the results obtained, it was also possible to evaluate the alternatives used in the process of re-contracting to restart the stalled works, and the impact of each of them on the time and cost of resuming construction, as well as the date of delivery of the works. work for society.